“Beta risk estimation of companies listed on the Ghana stock exchange - Quartey-Papafio, Anthony (2012)
A thesis submitted to the Department of Finance, Kwame Nkrumah University of Science and Technology, Kumasi in partial fullfilment of the requirements for the degree of Master of Business Administration (MBA) banking and finance.